2017
DOI: 10.1108/bfj-11-2016-0574
|View full text |Cite
|
Sign up to set email alerts
|

Which are the sustainable attributes affecting the real consumption behaviour? Consumer understanding and choices

Abstract: Purpose This is an exploratory study on consumer information and behaviour towards green, health, local, social and environmental credentials on labels. It focusses on many dimensions of sustainability in the food products that affect consumer choices with a dual purpose: to identify and define “sustainable consumption” behaviour in broad sense and to investigate empirically the factors affecting the real consumption behaviours. The purpose of this paper is to shed light on consumers’ understanding, motivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 34 publications
3
52
0
3
Order By: Relevance
“…Many researchers begin by assuming that labelling is one of the fundamental elements that push the consumer to choose a particular product and its subsequent repurchase, compared to another, thus determining a loyalty that leads to a competitive advantage for companies (Aprile and Annunziata 2006;Ilbery et al 2005;Mancini et al 2017). It is also certain that the correct production of a label allows a correct marketing of the product inside a country but also in relation to exports (Jansen and Lince de Faria 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many researchers begin by assuming that labelling is one of the fundamental elements that push the consumer to choose a particular product and its subsequent repurchase, compared to another, thus determining a loyalty that leads to a competitive advantage for companies (Aprile and Annunziata 2006;Ilbery et al 2005;Mancini et al 2017). It is also certain that the correct production of a label allows a correct marketing of the product inside a country but also in relation to exports (Jansen and Lince de Faria 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A strategic, multi-pronged, and multinational effort is necessary to enable and encourage consumers to adopt foods that are sustainably produced. On one hand, to embrace ethically produced foods, consumers must be aware of and care about the environmental and social effects of their own consumption behavior [71][72][73]. On the other hand, consumers often lack understanding of the influence that their food consumption habits can have on the environment, and this limits their ability to carry out ethical purchase behaviors [74,75].…”
Section: European and Uk Consumer Preferences For Eco-friendly Ricementioning
confidence: 99%
“…However, there remains no commonly agreed definition of "locally grown" or "regionally grown" food, and the definitions in the Australian context, have been under-researched. Varied definitions that are preferred by consumers have been reported [12][13][14][15][16]; some consumers may consider regionally grown food to be produced near where they live, whereas others may define it as grown in the same country where it is consumed. Despite these different definitions, research has shown that consumers have consistent expectations of regionally grown food.…”
Section: Introductionmentioning
confidence: 99%